EFEKTIVITAS PEMUNGUTAN PBB-P2 TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Arif Noerdwiansyah; Erwan Sutrisno (Jurnal Manajemen Dirgantara, 2024)
Local revenue is a source of revenue that is often used as an indicator of the progress of a region. Rural and Urban Land and Building Tax (PBB-P2) is one of the potential local tax revenues in Sleman Regency. This study aims to determine the level of effectiveness of the collection of Rural and Urban Land and Building Tax (PBB-P2) on the local revenue of Sleman Regency. The method used in this study is quantitative descriptive. The data used are primary data in the form of interviews with the Regional Finance and Asset Agency (BKAD) of Sleman Regency and secondary data in the form of reports on targets and realization of Rural and Urban Land and Building Tax (PBB-P2) revenues of Sleman Regency. The data analysis technique used is quantitative descriptive, while the analysis tool used in this study is effectiveness analysis. The results of the study indicate that the level of effectiveness of Rural and Urban Land and Building Tax (PBB-P2) revenues of Sleman Regency from 2018 to 2022 shows a very effective interpretation value criterion with an average of 103.48%.